SAGS AND FREQUENCIES OF NATURAL OSCILLATIONS OF COMPOSITE TWO-LAYER ISOTROPIC PLATES IN CASE OF CHANGE OF THICKNESS OF ONE OF THE LAYERS - Andrey, Turkov; Natalia, Abashina (Journal of Applied Engineering Science, 2018)
The article presents the results of a research of a composite isotropic two-layer plate of a square outline. We conduct the research for a number of plates with the variable thickness of layers and different conditions of fixing: pivotally supported and rigidly jammed on a circuit. By results of numerical researches we define the maximum sag of W0 from action of a static load and the frequency of natural cross oscillations ω of composite plates. By the results we define the proportionality coefficient K in a formula of the prof. V. I. Korobko. By the results of researches we construct the diagrams of change of the maximum sag and frequency of natural oscillations in case of change of thickness of layers of a composite plate.